Self-image and sexuality after mastectomy: a scoping review (Research, Society and Development, 2023)
Introduction: In Brazil, breast cancer ranks first in cancer mortality among women. In the year 2021, 66,280 new cases of breast cancer were diagnosed in the country. In the state of Rio Grande do Sul, 4,050 new cases were counted, with the highest rate of cases compared to the other southern states of the country, according to data from the National Cancer Institute this year.  Objectives: The objectives of this study were to examine and map the scientific evidence on self-image and sexuality in women after the mastectomy procedure. Methods: The study was designed as a scoping review proposed by the Jonna Briggs Institute (JBI), where we sought to map the main concepts that support this area of knowledge, examine the extent, scope and nature of the research, summarize and disseminate the research data and identify gaps in existing research. Results: We included 11 studies, published in the last five years, which involved as participants, women who had breast cancer and underwent mastectomy treatment. The contexts of interest were related to the breast cancer, mastectomy treatment and repercussions on the sexuality and corporal image of the women. The search was carried out in the bases of data, limiting itself to the articles published in Portuguese in the bases of data Scientific Electronic Library (SCIELO), and in the Portal of Periodicals of the Coordination of Improvement of Personnel of Superior Level (Capes). Conclusions: It is concluded that the loss of the breast due to mastectomy causes feelings which are harmful to mental health and a reduction in self-esteem, as well as harming the woman's sexual life. The fundamental role of the nursing team in welcoming and supporting mastectomized women is reinforced.